The HIV-1 Rev response element: An RNA scaffold that directs the cooperative assembly of a homo-oligomeric ribonucleoprotein complex - Fernandes, Jason (Landes Bioscience, 2012)
The HIV-1 Rev response element (RRE) is a ~350 nucleotide, highly structured, cis-acting RNA element essential for viral replication. It is located in the env coding region of the viral genome and is extremely well conserved across different HIV-1 isolates. It is present on all partially spliced and unspliced viral mRNA transcripts, and serves as an RNA framework onto which multiple molecules of the viral protein Rev assemble. The Rev-RRE oligomeric complex mediates the export of these messages from the nucleus to the cytoplasm, where they are translated to produce essential viral proteins and/or packaged as genomes for new virions.